2011
DOI: 10.1074/jbc.m110.180190
|View full text |Cite
|
Sign up to set email alerts
|

ATP Binding to Hemoglobin Response Gene 1 Protein Is Necessary for Regulation of the Mating Type Locus in Candida albicans

Abstract: HBR1 (hemoglobin response gene 1) is an essential gene inCandida albicans that positively regulates mating type locus MTL␣ gene expression and thereby regulates cell type-specific developmental genes. Hbr1p contains a phosphate-binding loop (P-loop), a highly conserved motif characteristic of ATP-and GTP-binding proteins. Recombinant Hbr1p was isolated in an oligomeric state that specifically bound ATP with K d ϳ2 M. ATP but not ADP, AMP, GTP, or dATP specifically protected Hbr1p from proteolysis by trypsin. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 38 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…HBR1 heterozygosis leads to an increased rate of opaque cell formation accompanying a turnoff of the MTL α2 gene and the ability to mate as an ‘a’ cell [ 18 , 19 ]. Hbr1 possesses a nucleotide-binding P-loop that is ATP-specific and is necessary for trypsin-resistance of the purified protein [ 20 ]. The human ortholog AD-004 (CINAP, ADK6) was originally identified as a binding partner of the Cajal body component coilin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HBR1 heterozygosis leads to an increased rate of opaque cell formation accompanying a turnoff of the MTL α2 gene and the ability to mate as an ‘a’ cell [ 18 , 19 ]. Hbr1 possesses a nucleotide-binding P-loop that is ATP-specific and is necessary for trypsin-resistance of the purified protein [ 20 ]. The human ortholog AD-004 (CINAP, ADK6) was originally identified as a binding partner of the Cajal body component coilin.…”
Section: Introductionmentioning
confidence: 99%
“…Adk6 possesses both adenylate kinase and ATPase activities [ 21 , 22 ]. However, Hbr1 possesses neither of these activities [ 20 ]. The S .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study identified amino acid residues important for mating locus regulation, but not for vegetative growth. Thus, amino acids identified to be important in model fungal species do not always translate to related pathogenic fungi (Peterson et al, 2011).…”
Section: Gene Function-essential Genesmentioning
confidence: 99%
“…It was known that HBR1 induced mating type genes, but mating is not an essential process in C. albicans (Peterson et al, 2011). Sites required for optimal growth and the oxidative stress response in the homologous gene in Saccharomyces were targeted in the C. albicans gene.…”
Section: Gene Function-essential Genesmentioning
confidence: 99%